EDUCATION 4.0: HYBRID LEARNING AND MICROLEARNING IN A SMART ENVIRONMENT: Received: 20th August 2021; Revised: 05th December 2021, 10th March 2022, 17th March 2022; Accepted: 22nd March 2022 - Mekacher, Leila (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The term "4.0" refers here, as in all areas whether Industry 4.0, Work 4.0, or Society 4.0, to the paradigm of digitalization and support through new technologies. In the last few years, education and training are becoming more closely related to the labor market, and so the goal is to foster competent learners to meet the core skills for life and work in the 21st century. Building such a future-ready education system requires the design of curricula, that impart the necessary knowledge and skills for the modern workplace. The various pedagogical and technological innovations in recent years have created new concepts of learning environments, that optimize learners’ ability to learn. They are commonly referred to as "smart learning environments". Innovative education based on advanced technologies should focus on stimulating thinking and creativity and address the individual differences of learners. The purpose of this paper is twofold. First, combines some educational concepts such as micro and hybrid learning with the support of immersive technologies to develop smart learning environments for a personalized and gamified seamless learning experience. Second, demonstrates how the concept of Micro-hybrid-immersive learning enables a seamless transition between school and the world of work and achieves educational inclusion.